2022
DOI: 10.3390/app12041996
|View full text |Cite
|
Sign up to set email alerts
|

Making Best Use of Home-Based Rehabilitation Robots

Abstract: Large-scale clinical trials have shown that rehabilitation robots are as affective as conventional therapy, but the cost-effectiveness is preventing their uptake. This study investigated whether a low-cost rehabilitation robot could be deployed in a home setting for rehabilitation of people recovering from stroke (n = 16) and whether clinical outcome measures correlated well with kinematic measures gathered by the robot. The results support the feasibility of patients independently using the robot with improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…A total of 45 studies 15,1721,23,2629,33,35,36,40,42,43,45,46,49,5256,6166,68,69,71,72,74,77–79,8285,89,91 deployed games for home-based upper limb rehabilitation following stroke. Of these, 15 articles 15,18,20,28,29,33,35,42,45,46,56,72,82,84,91 found a VR game to be a feasible, well-received, and safe intervention to use at home for people with chronic hemiparesis following stroke.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 45 studies 15,1721,23,2629,33,35,36,40,42,43,45,46,49,5256,6166,68,69,71,72,74,77–79,8285,89,91 deployed games for home-based upper limb rehabilitation following stroke. Of these, 15 articles 15,18,20,28,29,33,35,42,45,46,56,72,82,84,91 found a VR game to be a feasible, well-received, and safe intervention to use at home for people with chronic hemiparesis following stroke.…”
Section: Resultsmentioning
confidence: 99%
“…Patients have shown a high level of adherence, 97.8%, to gamificationmediated rehabilitative exercises. 101 This review identified 45,15,[17][18][19][20][21]23,[26][27][28][29]33,35,36,40,42,43,45,46,49,[52][53][54][55][56][61][62][63][64][65][66]68,69,71,72,74,[77][78][79][82][83][84][85]89,91 studies in which various types of digital games had been deployed as part of the intervention for homebased post-stroke upper limb rehabilitation. These games were augmented with/without virtual/immersive reality, and played via computer, mobile phone, and other digital devices and the participants were able to engage in rehabilitation activities based upon gamification within the home setting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations